A Study of Buluh Tumbang Community, Belitung: The Social Movements Antitheses Analysis - Djemahir, Arlina Arifin; Ariesta, Eliza; Siahaan, Ronny Rudolf; Wulandini, Wulandini (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Belitung Island has a long history in tin production and trading. The abundant tin content has attracted power from time to time to carry out exploitation. Although the victims are reportedly thinning tin, the news about the prediction of Thorium as a valuable mineral for energy production is expected to add to the history of mining in Belitung for thousands of years into the future. Several studies reveal that apart from having a positive impact, especially on the economy, mining also has a negative impact. Environmental degradation is getting worse every day and requires comprehensive handling. Although tin mining actually has a significant impact on the economic life of the community, mining activities do not guarantee a sustainable life for the community. The awareness that environmental damage is getting serious and worrying has not yet been collective-confrontational action directed at the responsible party. The common view of the people, government, and mining actors regarding economic dependence on tin affects the weakness of the framing process and the mobilization of reactions related to the problem of environmental damage. The contention of the people, government and mining actors took place in mutual compromise. This condition can threaten a threat to sustainable development. Contest analysis is needed to clarify the picture of the extent to which the dynamics of contestation can contribute to promoting sustainable development.